2014
DOI: 10.1016/j.sandf.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Displacements of column-supported embankments over soft clay after widening considering soil consolidation and column layout: Numerical analysis

Abstract: The common challenges for constructing embankments on soft clay include low bearing capacity, large total and differential settlements, and slope instability. Different techniques have been adopted to improve soft clay, such as the use of foundation columns including stone columns, deep mixed columns, and vibro-concrete columns, etc. Due to increased traffic volume, column-supported embankments may be widened to accommodate the traffic capacity need. Adding a new embankment to an existing embankment generates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Han et al (2007) found that the foundation columns play a good control effect on the differential settlement using the elastic-plastic finite element method. The same conclusion was obtained by Kamash & Han (2014). Yu et al (2017) adopted a numerical analysis method to consider the influence of the factors on settlement of existing embankment, including layouts of cement-fly ash-gravel (CFG) piles, strengths of CFG piles and filling materials of the new embankment.…”
Section: Research Progress Of Embankment Separated Widening and Isolating Wallmentioning
confidence: 63%
“…Han et al (2007) found that the foundation columns play a good control effect on the differential settlement using the elastic-plastic finite element method. The same conclusion was obtained by Kamash & Han (2014). Yu et al (2017) adopted a numerical analysis method to consider the influence of the factors on settlement of existing embankment, including layouts of cement-fly ash-gravel (CFG) piles, strengths of CFG piles and filling materials of the new embankment.…”
Section: Research Progress Of Embankment Separated Widening and Isolating Wallmentioning
confidence: 63%
“…El Kamash [6] used a two-dimensional difference numerical method to analyze the widened column-supported embankment on soft soil in the context of roadbed widening. Van Meurs [7] conducted a field study on the gap method for embankment widening.…”
Section: Introductionmentioning
confidence: 99%
“…This issue has attracted the attention of many engineers and researchers, and a handful of studies have been conducted to evaluate the geosynthetic-reinforced and semi-rigid column-supported embankments. These vary from laboratory tests (Chen et al, 2008a;Van Eekelen et al, 2012a, 2012bXu et al, 2016;Debnath and Dey, 2017;Esmaeili et al, 2017;Mehdizadeh et al, 2018) to full-scale experiments (Chen et al, 2010;Liu et al, 2012;Hong et al, 2014;Weng et al, 2014;Liu et al, 2015;Rowe and Liu, 2015;Van Eekelen et al, 2015;Cao et al, 2016;Van Eekelen et al, 2017;Michalowski et al, 2018;Tano et al, 2018;Wang et al, 2018aWang et al, , 2018c and from analytical models (Balaam and Booker, 1981;Deb, 2010;Karim et al, 2011;Van Eekelen et al, 2011Zhou et al, 2012;Yang et al, 2013;Zhuang et al, 2014;Jamsawang et al, 2016;Van Eekelen, 2016;Feng et al, 2017b;Zhao et al, 2017) to numerical simulations (Huang and Han, 2009;Jiang et al, 2014;Kamash and Han, 2014;Lai et al, 2014;Yoo, 2015;Zhuang and Wang, 2015;Liu et al, 2017;…”
Section: Introductionmentioning
confidence: 99%